Differentially expressed genes reflect disease-induced rather than disease-causing changes in the transcriptome - Eleonora Porcu (Nature Portfolio, 2021)
Identification of gene expression changes between healthy and diseased individuals can reveal mechanistic insights and biomarkers. Here, the authors propose a bi-directional transcriptome-wide Mendelian Randomization approach to assess causal effects between gene expression and complex traits.